2012
DOI: 10.3111/13696998.2012.756400
|View full text |Cite
|
Sign up to set email alerts
|

Comparative net cost impact of the utilization of romiplostim and intravenous immunoglobulin for the treatment of patients with immune thrombocytopenia in Québec, Canada

Abstract: Scarce blood products must be used wisely. Romiplostim can allow for improved healthcare resource allocation by reserving IVIg for use in other areas of greater need while also providing cost savings for the overall provincial healthcare budget.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In a study from Thailand (a developing country), cost effectiveness of IVIG in childhood ITP has been proven, as compared to standard treatment of thrombocyte transfusions, corticosteroids plus immunosuppressants ( 79 ). On the other hand, health economic studies from Canada and Ireland show for adult chronic ITP patients that romiplostim, a thrombopoietin receptor agonist, seems to compare favorably with standard treatment including IVIG ( 80 , 81 ).…”
Section: Immunomodulatory Therapymentioning
confidence: 99%
“…In a study from Thailand (a developing country), cost effectiveness of IVIG in childhood ITP has been proven, as compared to standard treatment of thrombocyte transfusions, corticosteroids plus immunosuppressants ( 79 ). On the other hand, health economic studies from Canada and Ireland show for adult chronic ITP patients that romiplostim, a thrombopoietin receptor agonist, seems to compare favorably with standard treatment including IVIG ( 80 , 81 ).…”
Section: Immunomodulatory Therapymentioning
confidence: 99%
“…Romiplostim has been shown to be cost effective compared with SoC and rituximab in other countries. In Canada, a net cost impact model showed that romiplostim is less expensive to prepare and administer than IVIg and is associated with lower indirect costs from a Canadian healthcare perspective [ 33 ]. Romiplostim was also associated with lower cost per response over 6 months when compared with rituximab from the French national health system perspective [ 34 ] and when compared with SoC in Spain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romiplostim is administered by subcutaneous injections in a dose based on a patient's body weight and platelet count. Romiplostim, however, is only available in two doses in prefilled vials, 250 µ g and 500 µ g, costing approximately $882.50 and $1765 Cdn, respectively [ 13 ]. The dose is potentially administered indefinitely for patients with chronic ITP.…”
Section: Discussionmentioning
confidence: 99%